1995
DOI: 10.1002/bbpc.19950990322
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Integrated Band Strength and Magnetic Dipole Transition Moments in the 2P3/22P1/2 Fine Structure (with Hyperfine Structure) Transition of the Iodine Atom: Experiment and Theory

Abstract: Previous experimental and theoretical results on the strength of the important fine structure transition in the Iodine atom scatter over a very wide range, indicating great uncertainty. We have therefore carried out new theoretical calculations and experiments to reinvestigate the transition probability between the fine structure levels 2P3/2 and 2P1/2 in the electronic ground configuration of atomic iodine. In the experiments a tunable, narrow band width, near‐IR laser was used to measure the iodine absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 43 publications
2
34
0
Order By: Relevance
“…The deviation at short range corresponds to a slightly smaller ⌬ so than for atomic iodine. 44 Such a reduction is not unexpected and was also observed for iodine in Xe matrices. 59 Finally we note that if one uses two of the neutral potentials to determine the third, i.e., allowing no variation in ⌬ so (R), then the repulsive wall of the generated potential deviates significantly from the ''best fit'' potential.…”
Section: B Fitting Proceduressupporting
confidence: 54%
See 1 more Smart Citation
“…The deviation at short range corresponds to a slightly smaller ⌬ so than for atomic iodine. 44 Such a reduction is not unexpected and was also observed for iodine in Xe matrices. 59 Finally we note that if one uses two of the neutral potentials to determine the third, i.e., allowing no variation in ⌬ so (R), then the repulsive wall of the generated potential deviates significantly from the ''best fit'' potential.…”
Section: B Fitting Proceduressupporting
confidence: 54%
“…1, we expect to observe two band systems, which are separated by approximately the spin-orbit constant of atomic iodine (0.942 65 eVϭ7603.0 cm Ϫ1 ). 44 The lower energy band system is shown in Fig. 2, and results from transitions to the X1/2 and I3/2 states.…”
Section: Zeke Spectra and Assignmentsmentioning
confidence: 99%
“…1 and our earlier studies of other diatomic and polyatomic rare gas halide species, we expect to observe two sets of features separated by approximately the spin-orbit splitting ⌬ so ͑I͒ of atomic iodine (7603.0 cm Ϫ1 ϭ0.942 65 eV). 46 The lower-energy features ͑Figs. 2-4͒ are due to transitions from the anion cluster to electronic states correlating with the 2 P 3/2 ground state of the iodine atom, and those at higher energy arise from transitions from the anion cluster to states referring asymptotically to the iodine 2 P 1/2 state ͑Fig.…”
Section: Zeke and Pdtp Resultsmentioning
confidence: 99%
“…The uncertainty of is estimated as 10% because it is also sensitive to systematic uncertainties in [O 2 ]. That leaves the following contributors to the uncertainty: , which has a relative uncertainty of 20% as reported by Ha et al 2 , and and 375 , which have 16 and 27% relative uncertainty, respectively, as shown in Table S1. Combining these uncertainties using the above equation…”
Section: Criegee Intermediate (Ci) Formation Rate Experimental Detailsmentioning
confidence: 91%